Integrating Carbohydrate and C1 Utilization for Chemicals Production. Issue 6 (17th January 2023) - Willers, Vivian Pascal; Beer, Barbara; Sieber, Volker
Abstract: In the face of increasing mobility and energy demand, as well as the mitigation of climate change, the development of sustainable and environmentally friendly alternatives to fossil fuels will be one of the most important tasks facing humankind in the coming years. In order to initiate the transition from a petroleum‐based economy to a new, greener future, biofuels and synthetic fuels have great potential as they can be adapted to already common processes. Thereby, especially synthetic fuels from CO2 and renewable energies are seen as the next big step for a sustainable and ecological life. In our study, we directly address the sustainable production of the most common biofuel, ethanol, and the highly interesting next‐generation biofuel, isobutanol, from methanol and xylose, which are directly derivable from CO2 and lignocellulosic waste streams, respectively, such integrating synthetic fuel and biofuel production. After enzyme and reaction optimization, we succeeded in producing either 3 g L −1 ethanol or 2 g L −1 isobutanol from 7.5 g L −1 xylose and 1.6 g L −1 methanol. In our cell‐free enzyme system, C1‐compounds are efficiently combined and fixed by the key enzyme transketolase and converted to the intermediate pyruvate. This opens the way for a hybrid production of biofuels, platform chemicals and fine chemicals from CO2 and lignocellulosic waste streams as alternative to conventional routes depending solely either on CO2 or sugars. Abstract : Waste to fuel : Artificial cell‐free enzyme cascade allows the synthesis of the common biofuel ethanol and next‐gen biofuel isobutanol from methanol and the second most abundant sugar in nature, xylose in one pot.